15th AIAA/CEAS Aeroacoustics Conference (30th AIAA Aeroacoustics Conference) 2009
DOI: 10.2514/6.2009-3298
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic Analysis of a Rod-Airfoil Flow by Means of Time-Resolved PIV

Abstract: Rod-Airfoil PIV Sound Acoustic Analogy Curle's Analogy Aeroacoustic analysis of a rod-airfoil flow by means of timeresolved PIV Left: Predicted wave fronts that are emanating from the airfoil Right: Predicted directivity pattern, green dots represent measurements Problem area The present paper investigates the feasibility of prediction of vortexstructure noise based on time resolved Particle Image Velocimetry (PIV). We consider the case of an airfoil immersed in the wake of a cylindrical rod.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…This will help considerably to understand the sound production mechanisms and to investigate possible ways to reducing it. A similar approach was applied previously by Lorenzoni (2008) on a rod-airfoil configuration. This gave promising result for this simple case.…”
Section: Discussionmentioning
confidence: 99%
“…This will help considerably to understand the sound production mechanisms and to investigate possible ways to reducing it. A similar approach was applied previously by Lorenzoni (2008) on a rod-airfoil configuration. This gave promising result for this simple case.…”
Section: Discussionmentioning
confidence: 99%
“…From the temporal evolution of the cross-correlation coefficient, the authors suggested that the source region was located by the leading edge of the airfoil. With a similar experimental approach, the far-field aeroacoustic of the rod-airfoil configuration was investigated by Lorenzoni et al (2009) who reported a favorable comparison for the tonal component between microphone measurements and predictions based on Curle's acoustic analogy (1955) applied to time-resolved planar PIV (TR PIV).…”
Section: Introductionmentioning
confidence: 99%
“…Except for computational approaches, no account has been made of the 3-D features in the flow due to intrinsic limitation of the planar two-and threecomponent PIV technique. In the investigation of the rod-airfoil flow, Lorenzoni et al (2009) stated that a noise prediction more accurate than that obtained assuming 2-D flow could be achieved if 3-D flow effects are taken into account. Also, in the same investigation, the low temporal resolution limited the accuracy of the evaluated instantaneous pressure, as well as of the pressure time rate of change, which is of prior importance for the evaluation of Curle's aeroacoustic analogy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations